Creating Ecoprint Batiks to Enrich Local Women's Economic Independence in Sidomulyo Village, Yogyakarta - Aji, Oktira Roka; Pratiwi, Ambar; Irsalinda, Nursyiva (OJS Universitas Muhammadiyah Gresik, 2025)
Sidomulyo Village in Bantul Regency, Yogyakarta, holds untapped potential in its rich biodiversity, particularly for economic empowerment among women, who comprise 53% of the population. The Women Skills Academy (WSA) were established with the aim of facilitating women's empowerment in Sidomulyo Village. In a previous program, training on ecoprint creation was conducted but several challenges were identified. These included limited diversity in ecoprint materials and designs, which restricted the ability to highlight the unique local identity of Sidomulyo Village. Furthermore, participation was predominantly limited to members of the Kelompok Wanita Tani (KWT), emphasizing the need to engage a wider spectrum of Women Skills Academy (WSA) members. To address these issues, the current program focuses on enhancing ecoprint techniques while incorporating e-commerce training. This integrated approach aims to empower participants with the skills needed to achieve economic independence and better represent the cultural richness of the village. The program included socialization, preparation, training, mentoring, and evaluation stages. The participants, guided by the community service team, significantly improved their knowledge and skills in both ecoprint production and online marketing, as shown by pre- and post-training evaluations. Participants successfully created ecoprint products using natural resources and learned to market these products via e-commerce platforms. Despite these achievements, challenges remain in diversifying materials, enhancing design uniqueness, and fully utilizing digital marketing. This program underscores the importance of leveraging local resources and providing continuous support to develop innovative, eco-friendly products that contribute to sustainable economic growth in rural communities.